The elusive and yet irrepressible modernist self: formulating a theory of self-reflexivity in Kurt Schwitters' Hanover Merzbau through the vitalist philosphies of Georg Simmel and Henri Bergson - Reynaga, Tahia Thaddeus (2004)
Kurt Schwitters decisively established that Dada was indeed more a state of mind than a collection of creeds. Spurned by Berlin Dada, he was compelled to construct for himself an alternative Dada existence, and this he accomplished in the one-man movement he christened "Merz". Hundreds of Merz artworks were produced by the tireless Schwitters, but the summa summarum of his oeuvre was the Hanover Merzbau (circa 1923-1943). As it transcends architecture, sculpture, and assemblage, I have taken the distinctive approach of analyzing it first and foremost in terms of a theory of self-reflexivity. The first and second chapters of this thesis are dedicated to the writings of Georg Simmel and Henri Bergson. The former contributes an understanding of the psyche of the modernist metropolitan and how it is that the subjective spirit that resides in this enlightened individual substantiates its existence by producing forms and objects with which it continuously comes into conflict. As witnessed in Schwitters' Merzbau, the self-conscious "I" constitutes a centripetal force that organizes and directs the objects it encounters and thus exerts a unifying influence over its environment. In the Bergson chapter, I pursue an in-depth investigation into how self-reflexivity is predicated upon the search for true duration and the manifestation of the elan vital. I also include an in-depth analysis of Bergson's treatise on laughter, for the theories contained within go a long way towards explicating Schwitters' brand of humour and how the comic artist is a self-reflexive figure non-pareil. The third chapter, devoted to Schwitters and his place in Dada, takes into account the vitalist philosophical underpinnings of the Merzbau and asserts that self-reflexive art operates under an enantiodromic law; the presence of the artist must be effaced as thoroughly as possible before the creative self achieves materialization in the artwork it has engendered.